The KONSTRUKSI MAKNA SELF HEALING MILLENIAL MOMS DI INSTAGRAM: KONSTRUKSI MAKNA SELF HEALING MILLENIAL MOMS DI INSTAGRAM - Sundari, Dini; Wirman, Welly; Yozani, Ringgo Eldapi (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2023)
ABSTRACT This research is motivated by the high dynamics of life affecting millennial moms for mental health disorders. So, every millennial moms really has the right to do self-healing or known as self-healing. Today's Digital Era has changed the way millennial moms view self-healing, which is very busy being carried out through Instagram social media with indications of sharing travel, care, shopping, quotes, and pouring out their hearts content. Millennial moms' familiarity with digital media is not in line with literacy skills which are considered to be still at a low level, so that the self-vulnerabilities experienced by millennial moms form an easy attitude to self-diagnose as sufferers of depression, stress and feel the need for self-healing. The purpose of this study is to find out the various meanings of self-healing behavior that millennial moms do on Instagram. The phenomenon of Self Healing Millennial Moms on Instagram can be studied through a phenomenological approach by applying symbolic interaction theory to reveal all the hidden meanings of the symbols depicted through self-healing actions of millennial moms on Instagram. This research also applies purposive techniques as the selection of informants. The data collection technique used in this study was through in-depth interviews, observation and documentation which were then analyzed through the stages of phenomenological research. The results of this study consist of the meaning of self-healing millennial moms via Instagram divided into three points according to the theory of symbolic interaction based on the Mind, namely self-healing as a form of self-healing process, self-pleasing, self-strengthening and self-disclosure. the second point is Self which means as a process of building positive suggestions, comparing oneself, building an image as a victim and the third point is Community, self healing means support. Key Word : Meaning, Self Healing, Millennial Moms, Instagram